Synthesis of Carboxymethyl Cellulose from Mangrove Nipah (Nypa fruticans) as Vitamin C Coating for Drug Delivery System - Delviani, Delviani; Maharani, Vioala Giary Rizkillah; Shadrina, Putri Nur; Ali, Noha; Tarigan, Indra Lasmana (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2024)
Vitamin C is one of the substances needed by the human body which acts as an antioxidant that effectively overcomes the effects of free radicals that damage cells in the body, but vitamin C has properties that are easily oxidized so that innovation is needed to coat (encapsulate) vitamin C in the form of capsules as a drug delivery system. One polymer that can be used for vitamin C encapsulation is cellulose. The cellulose content can be found in the skin and nipah fruit and then synthesized into carboxymethyl cellulose as a vitamin C coating. The microencapsulation method was carried out by mixing 3 g of carrageenan-CMC mixture with variations in the ratio of 1:0; 1:0.5 and 1:1 (%b/b). The encapsulated small beads were made in 200 mL of 2M KCl-CaCl solution by extrusion technique. The microencapsulant was then drained and continued with the crosslinking stage using Glutaraldehyde (GA) 1%. In this in vitro oral simulation study, the encapsulation ratio that produced the best treatment with the highest percentage of drug solubility in the intestine was the ratio (1:0.5), followed by (1:1) and the smallest (1:0) with percentage values of 15.42; 14.06; and 1.67 percent, respectively.